Exploring the Invariant Core: An Analysis of Multiple Translations of a Selection from Iqbal’s Shikwah - Nasir Mehmood; Hazrat Umar (بازیافت, 2020)
This paper is an attempt to explore the invariant core among the three English translations of selected poetry from Iqbal’s Shikwah. The study identifies that the complex nature of poetry makes it difficult for the translators to transfer the ST in terms of both content and form. Therefore, good poetry is translated not only once, but several times by different translators with their different approaches and strategies. Accordingly, Iqbal’s Shikwah and Jawab -e- Shikwah is translated by three translators, including two foreign and one indigenous translator. This is a qualitative research, and Viney and Darbelnet’s model of translational analysis was used as it best suited the qualitative nature of the present research. The study was delimited to the three selected translations of a stanza from Iqbal’s famous poem Shikwa rendered by the three translators Arbury, Singh, and Akhtar. The analysis of the translations has shown that in rendering the original text, the translators have used different procedures and strategies which consequently resulted in various losses, specifically in terms of form, however, the invariant core, which comprises both theme and tone, remains almost the same.